Crystallization and preliminary crystallographic analysis of an Escherichia coli‐selected mutant of the nuclease domain of the metallonuclease colicin E7. Issue 5 (22nd May 2013) - Czene, Anikó; Tóth, Eszter; Gyurcsik, Béla; Otten, Harm; Poulsen, Jens‐Christian N.; Lo Leggio, Leila; Larsen, Sine; Christensen, Hans E. M.; Nagata, Kyosuke
<x xml:space="preserve">Abstract</x> The metallonuclease colicin E7 is a member of the HNH family of endonucleases. It serves as a bacterial toxin in Escherichia coli, protecting the host cell from other related bacteria and bacteriophages by degradation of their chromosomal DNA under environmental stress. Its cell‐killing activity is attributed to the nonspecific nuclease domain (NColE7), which possesses the catalytic ββα‐type metal ion‐binding HNH motif at its C‐terminus. Mutations affecting the positively charged amino acids at the N‐terminus of NColE7 (444–576) surprisingly showed no or significantly reduced endonuclease activity [Czene et al. (2013), J. Biol. Inorg. Chem.18, 309–321]. The necessity of the N‐terminal amino acids for the function of the C‐terminal catalytic centre poses the possibility of allosteric activation within the enzyme. Precise knowledge of the intramolecular interactions of these residues that affect the catalytic activity could turn NColE7 into a novel platform for artificial nuclease design. In this study, the N‐terminal deletion mutant ΔN4‐NColE7‐C* of the nuclease domain of colicin E7 selected by E. coli was overexpressed and crystallized at room temperature by the sitting‐drop vapour‐diffusion method. X‐ray diffraction data were collected to 1.6 Å resolution and could be indexed and averaged in the trigonal space group P3121 or P3221, with unit‐cell parameters a = b = 55.4, c = 73.1 Å. Structure determination by molecular replacement is in progress.